2013
DOI: 10.1002/jmri.24446
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of MRI renal artery blood flow and BOLD measurements in patients with chronic kidney disease and healthy controls

Abstract: The reproducibility was high for both RABF and R2 * in patients and controls, particularly in the cortex. Inhalation of 100% oxygen reduced medullary R2 *.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 33 publications
7
51
0
Order By: Relevance
“…In contrast, Djamali et al 37 utilized BOLD MRI to demonstrate increased oxygenation in the renal medulla and cortex of subjects with CKD due to chronic allograft nephropathy. To add to this confusion, both Siddiqi et al 38 and Khatir et al 17 found no difference in renal cortical or medullary oxygenation in subjects with CKD (n=10 and n=11, respectively) versus healthy controls.…”
Section: Diabetic Nephropathymentioning
confidence: 96%
See 3 more Smart Citations
“…In contrast, Djamali et al 37 utilized BOLD MRI to demonstrate increased oxygenation in the renal medulla and cortex of subjects with CKD due to chronic allograft nephropathy. To add to this confusion, both Siddiqi et al 38 and Khatir et al 17 found no difference in renal cortical or medullary oxygenation in subjects with CKD (n=10 and n=11, respectively) versus healthy controls.…”
Section: Diabetic Nephropathymentioning
confidence: 96%
“…35 Angiotensin II inhibitors and angiotensin receptor blockers would be expected to increase intrarenal oxygenation by increasing oxygen delivery due to increased renal blood flow, by decreasing oxygen consumption due to decreased filtration fraction and reduced filtered sodium load, and by increasing the efficiency of oxygen utilization due to reduced generation of reactive oxygen species. 17 These agents ameliorate renal hypoxia in experimental models of diabetes mellitus, in the remnant kidney, and in angiotensin II-mediated models of hypertension, independent of blood pressure control. 17 Administration of angiotensin II to healthy male subjects examined by BOLD MRI (n=6) led to renal hypoxia.…”
Section: Angiotensin IImentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from in patients with significant anatomical variations, this technique has been shown to correlate well with a number of alternative measures of renal blood flow [21]. In 11 patients with CKD (mean creatinine 21578mol/l) PC-MRI was used to measure RBF, and showed good reproducibility (coefficient of variation (CoV) of 12.9%), with RBF being significantly lower in CKD patients as compared with healthy volunteers [22]. Interestingly, the reproducibility of BOLD-MRI was better in the same cohort of patients (CoV of 8.0 %).…”
Section: Phase Contrast Mrimentioning
confidence: 99%